2023
DOI: 10.1177/15248380231162967
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-informed Interventions in Early Childhood Education and Care Settings: A Scoping Review

Abstract: Trauma in early childhood is a significant public health concern. Early Childhood Education and Care (ECEC) services are uniquely positioned to buffer the negative impact of early childhood trauma on children. This scoping review synthesized studies evaluating trauma-informed interventions in ECEC settings through a systematic search of four relevant online databases (PsycINFO, Medline, ERIC, A+ Education). Fourteen studies met the inclusion criteria, with 12 ECEC center-based trauma-informed interventions eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…An encouraging recent study reported that a well-being intervention involving coaching, relaxation, nutrition, and physical activity was especially beneficial in improving the classroom-based positive affect of ECEs with high ACE levels ( Stone et al, 2023 ). In a systematic review of trauma-informed interventions delivered to ECEs, there were positive benefits to ECE’s trauma awareness, knowledge and practices ( Sun et al, 2023 ). However, many interventions focus on understanding young children’s experience of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…An encouraging recent study reported that a well-being intervention involving coaching, relaxation, nutrition, and physical activity was especially beneficial in improving the classroom-based positive affect of ECEs with high ACE levels ( Stone et al, 2023 ). In a systematic review of trauma-informed interventions delivered to ECEs, there were positive benefits to ECE’s trauma awareness, knowledge and practices ( Sun et al, 2023 ). However, many interventions focus on understanding young children’s experience of trauma.…”
Section: Discussionmentioning
confidence: 99%